UPAYA PENINGKATKAN HASIL BELAJAR PADA MATERI DAMPAK PENJAJAHAN BANGSA EROPA DENGAN MODEL PEMBELAJARAN COOPERATIVE LEARNING TIPE MAKE A MATCH PADA SISWA KELAS XI-IPS DI SMA NEGERI 1 PEUDAWA KABUPATEN ACEH TIMUR - Halimatussakdiah Halimatussakdiah (Education Enthusiast : Jurnal Pendidikan dan Keguruan, 2021)
This research is a Classroom Action Research (PTK). This research was conducted in class XI-IPS at SMA Negeri 1 Peudawa, East Aceh Regency, odd semester, 2020/2021 school year. Students who were used as research objects were 27 students of class XI-IPS. This study aims to improve learning outcomes on the impact of the European colonialism with the make a match cooperative learning model for class XI-IPS at SMA Negeri 1 Peudawa, East Aceh Regency. This research was conducted through two cycles. From the results of learning improvements that have been carried out through classroom action research, it can be concluded that: 1. There are differences in student learning outcomes between the use of the lecture method and the Make-A Match type of Cooperative Learning model. 2. There is an increase in learning outcomes, namely the written ability of students both seen from the average value and learning completeness from cycle to cycle shows a significant increase. The average score of students in the pre-cycle was only 69.2, then in the first cycle it increased to 72.1, and in the second cycle it increased to 80.7. Furthermore, in the pre-cycle students who completed only 40.7%, then in the first cycle it increased to 70.4%, and in the second cycle it increased to 96.3%.Keywords: political, cultural, social, and economic impact, make a match model